ANALYSIS OF EMPLOYE TURNOVER FACTORS ON WORK EFFECTIVENESS THROUGH RISK CONTROL AT BPJS KETENAGAKERJAAN - Mughny Ilman Wali Rusdi; Nimmi Zulbainarni; Asep Taryana (Pena Cendekia Insani, 2025)
This study aims to analyze the influence of employe turnover factors on work effectiveness thru risk management at BPJS Ketenagakerjaan. The factors studied include job satisfaction, compensation, workload, role ambiguity, and relationships with supervisors. This research uses a quantitative approach with the Structural Equation Modeling Partial Least Square (SEM-PLS) method and Bow Tie Analysis. The sample consisted of 251 active BPJS Ketenagakerjaan employes selected using purposive sampling technique. The data collection instrument uses a Likert scale-based questionnaire. Validity and reliability were tested thru outer loading, construct reliability, and AVE, as well as discriminant validity thru HTMT and the Fornell-Larcker Criterion. The results show that all five turnover factors significantly affect work effectiveness, both directly and thru risk management. The variables of job satisfaction (? = 0.379, p = 0.000) and relationship with superiors (? = 0.173, p = 0.016) have a significant positive influence. Conversely, workload (? = -0.149, p = 0.000) and role ambiguity (? = -0.117, p = 0.000) have a negative influence. Risk control was also proven to be a significant mediator. The R² value of 0.778 for work effectiveness indicates the model's strong predictive ability. This research integrates the SEM-PLS approach with Bow Tie Analysis in the context of public organizations, and provides an empirical contribution to turnover risk control strategies to improve work effectiveness.